Propuesta metodológica para fomentar la igualdad de género en el aula escolar - Solís Pérez, Yisenia (Revista Electrónica Educare, 2006)
This work is named methodological proposed to fortify the equality of kind in the school classroom, with children and girls of the primary school. As teacher, I have wanted to contribute through my lived experiencies, some strategies that they allow to foment in ours students a more just and egalitarian education. Knowledgeable, of the different sexist practices and stereotypes highly established in our society, that hinder some women manage to be unfold according to their own capacities and potentials, bordering them to comply with the role that the society assigns them according to their sex, it is that I desire to put an propose in order the students live in the classroom a real equality. Being the school one of the more important agents of socialization, and where it is necessary to propitiate the change in favour of an education of equity. The work to level of classroom will allow diminishing the discriminatory schemes and will be a great achievement in benefit of the future generations. The interrelationships that live in that small culture called classroom, are very wealth-producing and varied, for which it is a favourable place to initiate changes in matter of kind.